Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1889)
Demorest's Family Magazine. April 1889. Vol. 25, no. 6. -- New York One Hundred Years Ago -- The Alpine Fay: A Romance -- An April Chronicle -- The Laggard Letter's Luck -- The Club of the Future: Men and Women's Clubs, Their Possibilities and Prospects -- What Katy Did -- Young Japan at Play -- Practical Etiquette: Wedding Anniversaries -- Our Girls: Pleasant Reading for Sweet Seventeen -- Home Art and Home Comfort: Easter-Egg Tea-Seats, and Other Ornaments -- The Worlds's Progress -- What Women are Doing -- Chat -- How My Sick Neighbor Rallied -- Household: Graded Establishments III. Homes with Two Servants -- Going to the New Home: How to Pack and Move -- The Martyr's Daughter: Easter Morning -- Mirror of Fashions: Review of Fashions - April -- Prohibition the Acme of Love, Law, and Liberty -- Mrs. Caroline Elizabeth Merrick -- The Battle Cry Must be Prohibition -- The Effects of Prohibition -- Correspondence Club -- Spice Box
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print. Valdosta State University Archives and Special Collections. May 11, 2017. Original document ends on page 410.
Keywords: Fashion; Travel; Illustrated Periodicals; Catalogue; Children; Magazine; 1800s; 19th Century; Homemaking; Needlework; Dressmaking; Women's History; Social History; Fashion; United States